THE (NON) INCIDENCE OF ISS – SERVICE TAX ON ACTIVITIES CARRIED OUT ON SOCIAL NETWORKS: AN ANALYSIS OF THE JUDGMENT OF THEME 296 BY THE FEDERAL SUPREME COURT - Afonso Côrtes, Leonardo; Augusto Bizestre Orlato, Gerson (Revista Gênero e Interdisciplinaridade, 2023)
With the advent of the internet and the evolution of social networks there have been numerous changes in people's behavior, especially with the emergence of new business formats, one of which is the digital influencer, so much so that the Ministry of Labor included the profession in the Classification Brazilian Occupations. The question is to know which services are provided by the Digital Influencer and whether they are a hypothesis of Service Tax, including the new decision of the Federal Supreme Court that established that the list of services is exhaustive, allowing for an extensive interpretation.